2021
DOI: 10.1002/etc.5017
|View full text |Cite
|
Sign up to set email alerts
|

Silver Ion Release Accelerated in the Gastrovascular Cavity of Hydra vulgaris Increases the Toxicity of Silver Sulfide Nanoparticles

Abstract: Silver nanoparticles (Ag-NPs) streamed into aquatic environments are chemically transformed into various forms, and one of the predominant forms is silver sulfide NPs (Ag 2 S-NPs). Because of the lower dissolution rate of silver ions (Ag + ), the toxicity of Ag 2 S-NPs could be lower than that of Ag-NPs. However, the toxicity of Ag 2 S-NPs has been observed to be restored under oxidative or acidic conditions. In the present study, 4 aquatic organisms, Pseudokirchneriella subcapitata (algae), Daphnia magna (cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The release of ions goes to the physiological environment, and different studies have observed that they can be stored in different organs. The threshold concentrations that can cause toxicity in humans are not known, and at the moment, the quantities of ions are compared to those we ingest in our daily diet [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…The release of ions goes to the physiological environment, and different studies have observed that they can be stored in different organs. The threshold concentrations that can cause toxicity in humans are not known, and at the moment, the quantities of ions are compared to those we ingest in our daily diet [56][57][58].…”
Section: Discussionmentioning
confidence: 99%
“…In complex microcosms, nearly 100% of Ag was bound to sulfur, which decreased the bioavailability and toxicity of Ag + and AgNPs 77 . Another study also showed that Ag Hydra vulgaris (cnidarian) was detected 79 . Our studies demonstrated the possibility that the anaerobic gut environment of D. magna provided an ideal condition for the gut-microbial transformation of Ag + and AgNPs through sulfidation with enriched sulfate and sulfate reducing bacteria 80 , since low oxygen is one of the requirements for microbial sulfate reduction 81 .…”
Section: Sulfidation and Organic Degradation Based On Gut-microbial Transformation And Adaptationmentioning
confidence: 91%
“…The low release of Ag ions in Hydra medium, as shown by ICP-MS data, surely played a significant role in the observed reduced ecotoxicity, also based on the morphological effects observed upon exposure to AgNO 3 , confirming the sensitivity of Hydra to Ag. However, Kang and Park [30] measured high levels of Ag inside Hydra specimens exposed to sulfide-coated AgNPs (Ag 2 S-NPs), even if the nominal dissolution of AgNPs in the medium was as low as non-detectable (LOD not reported). This was associated with toxicity, both at the morphological and regeneration levels (with EC 50 of 0.65 and 0.09 mg/L, respectively).…”
Section: Ecotoxicitymentioning
confidence: 99%
“…This was associated with toxicity, both at the morphological and regeneration levels (with EC 50 of 0.65 and 0.09 mg/L, respectively). The authors hypothesized the ingestion of Ag 2 S-NPs followed by dissolution, triggered by the acidic environment of the gastrovascular cavity [30].…”
Section: Ecotoxicitymentioning
confidence: 99%